A multicenter study evaluating the frequency and time requirement of mechanical thrombectomy. (9th June 2017) - Wilson, Taylor A; Leslie-Mazwi, Thabele; Hirsch, Joshua A; Frey, Casey; Kim, Teddy E; Spiotta, Alejandro M; Leacy, Reade de; Mocco, J; Albuquerque, Felipe C; Ducruet, Andrew F; Cheema, Ahmed; Arthur, Adam; et al.
Abstract : Introduction: There are few published data evaluating the incidence of mechanical thrombectomy among stroke centers or the times at which they occur. Methods: A multicenter retrospective study was performed to identify all patients undergoing emergent thrombectomy for acute ischemic stroke during a 3-month period (June through August 2016). Consultations that did not undergo thrombectomy were not included. Results: Ten institutions participated in the study. During the 92-day study period, a total of 189 patients underwent mechanical thrombectomy. The average number of procedures per hospital over the study period was 18.9 (average of 0.2 cases per day per or 75.6 cases per year). This ranged from 0.09 cases per day at the lowest volume center to 0.49 cases per day at the highest volume center. Procedures were more common on weekdays (p<0.001) and during non-work hours (p<0.001). The most common period for thrombectomy procedures was between 20:00 and 21:00 hours. The median time from notification to groin puncture was 84 min (IQR 56–145 min) and from puncture to closure was 57 min (IQR 33–80 min). The median time from imaging completion to procedural start was 52 min longer for non-work hours than during work hours (p<0.001). There were no differences in procedural length based on day of the week or time of day. Conclusions: These findings indicate that the majority of mechanical thrombectomy cases occur during non-work hours, with associated off-hours delays, which has important operational implications for hospitals implementing stroke call coverage.